Chlamydia trachomatis developmentally regulated protein is homologous to eukaryotic histone H1. - Hackstadt, T (1991)
Chlamydiae are prokaryotic obligate intracellular parasites that undergo a biphasic life cycle involving an infectious, extracellular form known as elementary bodies and an intracellular, replicating form termed reticulate bodies. We have purified from Chlamydia trachomatis a very basic elementary body-specific protein with an apparent molecular mass of 18 kDa, determined its N-terminal amino acid sequence, and cloned the encoding gene. Sequence analysis of the cloned gene revealed some remarkable properties for its expressed product, including a high lysine content (29%), a correspondingly high pI, and significant homology to the H1 class of eukaryotic histones. Furthermore, a monoclonal antibody to this chlamydial histone analog, termed Hc1, displayed immunoblot and antinuclear specificity suggestive of cross-reactivity to H1 histones. The gene was expressed only during the late stages of the chlamydial life cycle concomitant with the reorganization of chlamydial reticulate bodies into elementary bodies, suggesting that the Hc1 protein plays a role in the condensation of chlamydial chromatin during intracellular differentiation.